Caracterización del perfil de ácidos grasos de la carne de Pacú (Pyaractus mesopotamicus) - Montenegro, Luciano Federico (2019)
Pyaractus mesopotamicus (Pacú) is the most produced freshwater species in Argentina. The objective was to determine the fatty acid composition of pacú meat fed with commercial diet. The main fatty acids were those belonging to the MUFA and SFA groups. The EPA + DHA concentrations detected would allow to cover important proportions of the recommended daily intake for human beings.